Pengaruh Harga, Pelayanan dan Store Atmosphere Terhadap Kepuasan Pelanggan Diva Store - Nandyto Pramudya Pratama; Nurhidayah Nurhidayah; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Along with the development of the era, innovation continues to be carried out in the field of technology and industry. Likewise, the clothing industry is growing rapidly in Indonesia. The fashion industry will continue to grow along with the development of the industry and the fashion itself. The fashion industry is very flexible because at a certain time or season it has certain characteristics as well so that it is very dependent on the trends that occur at that time or season. Technological developments, especially in the industrial sector, will open up greater opportunities to be creative in the fashion sector. Diva Store is a form of business engaged in the fashion sector, especially in the sale of apparel and accessories for all walks of life. Diva Store is a reference store in the Blitar area due to good service and affordable prices. The purpose of this study was to determine the simultaneous effect of price, service, and store atmosphere on Diva Store customer satisfaction. The population in this study were Diva Store customers who had made purchases more than 2 times and had a job status. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sample collection technique based on certain criteria using a questionnaire distributed to 80 respondents and using the SPSS analysis tool. The results of the study show that partially the price, service, and store atmosphere have a significant effect on Diva Store customer satisfaction. Simultaneously price, service, and store atmosphere have a significant effect on Diva Store customer satisfaction. Keywords: Price, Service, and Store Atmosphere